well of course if
T(t) = 2+23e^kt
T(10) will not equal T(30)
You sure they're both supposed to be 17?
So, what was the original problem?
Okay, so
I worked out
17 = T(10) = 2 + 23e ^10k
15/23 = e^10k
k= 1/10ln(15/23)
k = - 0.043
But when I do this equation
17 = T(30) = 2 + 23e^30k
15/23 = e^30k
k = 1/30ln(15/23)
k = -0.142
But the answer is apparently 8.38?
Can someone please help.
I think I'm getting too tired and I can't pick up on my mistakes. =(
4 answers
Suppose that the temperature of the environment is 2 degrees and the initial temperature of the object is 25 degrees. After 10 minutes the temperature of the object is observed to be 17 degrees.
what is the temperature of the object after 30 minutes?
after how many minutes is the temperature of the object 4 degrees?
what is the temperature of the object after 30 minutes?
after how many minutes is the temperature of the object 4 degrees?
As I recall, you need Newton's law of cooling, which in this case would be
T(t) = 2+23e^(-kt)
where we try use a positive k.
T(10) = 17, so
2+23e^(-10k) = 17
k = 0.0427
and we have T(t) = 2+23e^(-.0427t)
So, after 30 minutes,
T(30) = 2+23e^(-.0427*30) = 8.388
When T=4, we have
2+23e^(-.0427t) = 4
t = 57.20
T(t) = 2+23e^(-kt)
where we try use a positive k.
T(10) = 17, so
2+23e^(-10k) = 17
k = 0.0427
and we have T(t) = 2+23e^(-.0427t)
So, after 30 minutes,
T(30) = 2+23e^(-.0427*30) = 8.388
When T=4, we have
2+23e^(-.0427t) = 4
t = 57.20
Ahhhhh! Okay awesome! Thank you!
Makes so much sense!
Makes so much sense!